2018
DOI: 10.1002/jcb.27819
|View full text |Cite
|
Sign up to set email alerts
|

Application of iTRAQ proteomics in identification of the differentially expressed proteins of placenta of pregnancy with preeclampsia

Abstract: Objective To explore the differential protein profile of preeclampsia and identify its potential biomarker. Methods Around 20 pregnant women with preeclampsia (preeclampsia group) and 20 normal‐term pregnancy (normal group) were collected from 2017 to 2018 in the study. Total protein of placenta tissues was extracted, denaturized, deoxidized, and enzymolyzed. The sample was labeled with isobaric tags for relative and absolute quantitation (iTRAQ) and analyzed with mass spectrum to identify differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The high metabolic rate is needed for hormone biosynthesis and metabolism as well as nutrient transport, which are key functions of the STB. Several studies have exploited MS and NMR-based technologies using placental tissue to screen for changes in the proteome and metabolome in normal pregnancies and those in various other conditions such as obesity, neural tube defects, high altitude, preeclampsia, and gestational diabetes ( Van Patot et al, 2010 ; Chi et al, 2014 ; Austdal et al, 2015 ; Yang et al, 2015 ; Mary et al, 2017 ; Qi et al, 2017 ; Fattuoni et al, 2018 ; Sun et al, 2018 ; Feng et al, 2019 ). Using GC-MS and ultra-performance LC-MS, Dunn et al (2012) found changes in 156 metabolites between early and late-gestation placentas, including increased levels of diglycerides, phospholipids, sphingolipids, and vitamin D-related metabolites, as well as decreased levels of triglycerides in late gestation placental tissue.…”
Section: Using Omics To Define the Stb Metabolome And Sub-proteomementioning
confidence: 99%
“…The high metabolic rate is needed for hormone biosynthesis and metabolism as well as nutrient transport, which are key functions of the STB. Several studies have exploited MS and NMR-based technologies using placental tissue to screen for changes in the proteome and metabolome in normal pregnancies and those in various other conditions such as obesity, neural tube defects, high altitude, preeclampsia, and gestational diabetes ( Van Patot et al, 2010 ; Chi et al, 2014 ; Austdal et al, 2015 ; Yang et al, 2015 ; Mary et al, 2017 ; Qi et al, 2017 ; Fattuoni et al, 2018 ; Sun et al, 2018 ; Feng et al, 2019 ). Using GC-MS and ultra-performance LC-MS, Dunn et al (2012) found changes in 156 metabolites between early and late-gestation placentas, including increased levels of diglycerides, phospholipids, sphingolipids, and vitamin D-related metabolites, as well as decreased levels of triglycerides in late gestation placental tissue.…”
Section: Using Omics To Define the Stb Metabolome And Sub-proteomementioning
confidence: 99%
“…Some scholars have proposed a two‐stage model of PE: stage 1 is poorly perfused placenta in the first trimester, wherein the failure of trophoblast invasion leads to dysfunctional spiral artery remodelling, and hypoxia may cause oxidative stress and imbalance of reactive oxygen species in the placenta of PE; stage 2 is a maternal syndrome in the last second and third trimesters characterized by angiogenesis imbalance, inflammatory cytokines and immune cell alterations 4,5 . The placental tissue is directly exposed to the uterine decidua, which is involved in maternal–foetal immune tolerance and pregnancy maintenance 6 . Although its exact pathogenesis and triggering conditions are still not fully clarified, it is widely believed that the placenta plays a central role in PE formation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a lack of available studies on the role of Kac modification in PE. Previous researchers have used iTRAQ proteomics to identify differentially expressed proteins (DEPs) in PE and normal pregnancy placental tissues to look for potential biomarkers of PE 6 . Quantitative analysis and PTMs of proteins are essential for understanding biological complexity 12,18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations